2021
DOI: 10.1128/msphere.00850-21
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Analysis of bla KPC-2 -Harboring Plasmids: Tn 4401a Interplasmid Transposition and Tn 4401a -Carrying ColRNAI Plasmid Mobilization from Klebsiella pneumoniae to Citrobacter europaeus and Morganella morganii in a Single Patient

Abstract: Plasmid transfer plays an important role in the interspecies spread of carbapenemase genes, including the Klebsiella pneumoniae carbapenemase (KPC)-coding gene, bla KPC . We conducted whole-genome sequencing (WGS) analysis and transmission experiments to analyze bla KPC-2 -carrying mobile genetic elements (MGEs) between the bla KPC-2 -harboring K. pneumoniae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
1
3
0
Order By: Relevance
“…Resistance genes for cotrimoxazole (sul or dfrA) were found in all isolates except one. The Inc-type plasmids detected in all isolates and the Col-type plasmids detected in 15 isolates have been reported in other studies [21,59].…”
Section: Discussionsupporting
confidence: 85%
“…Resistance genes for cotrimoxazole (sul or dfrA) were found in all isolates except one. The Inc-type plasmids detected in all isolates and the Col-type plasmids detected in 15 isolates have been reported in other studies [21,59].…”
Section: Discussionsupporting
confidence: 85%
“…These plasmids contained a wide range of transposable elements that enabled them to undergo frequent genetic transposition ( 24 ). Kayoko Sugita elaborated on the interplasmid transposition of bla KPC-2 -containing Tn4401a from an IncN+R plasmid to a ColRNAI plasmid in Klebsiella pneumoniae ( 25 ). In this study, while the detection rate of the carbapenemase genes in M. morganii was relatively low, we found that most of these genes were harbored within plasmids.…”
Section: Discussionmentioning
confidence: 99%
“…These plasmids can be important vectors for transferring antimicrobial resistance genes between isolates, including the transfer of bla KPC -type carbapenemases ( 19 , 31 , 62 ). Experimentally, ColRNAI plasmids encoding bla KPC and Tn 4401 could mobilize between strains and participate in Tn 4401 transposition events within a patient ( 63 ). About half the plasmids we sequenced in this primary cluster do not encode a relaxase but they could be mobilized by the relaxase of a co-resident plasmid if the oriT sequence has enough similarity as shown in a previous study ( 64 ).…”
Section: Discussionmentioning
confidence: 99%